Collaborating for Coherence around Social Justice: Leveraging Accreditation to Conceptually Transform from a Diversity Requirement to a Social Justice Orientation. Issue 4 (2nd October 2019) - Ford, Amy Carpenter; Cunningham, Kevin D.; Lewsader, Joellen; Jasper, Andrea D.; Heroux, Jodell; Wirz-Palacios Klemm, Jennifer
ABSTRACT: In this article, we describe teacher educators' collaboration for coherence around social justice teacher education in preparation for a national accreditation review. Specifically, we illuminate how we cultivated an inquiry stance and critical conversations to build a safe and trusting community, generate locally meaningful values, and reconceptualize diversity in terms of social justice. By depicting our collaborative process in clarifying a detail, we make visible how we developed social justice-oriented vision, mission, and commitment statements and a conceptual framework to transform our traditional university-based undergraduate program. Aiming to inform other programs striving for coherence for social justice, we offer insights for supporting collaboration, considering the local community and political context, and leveraging accreditation.